Rancang Bangun Sistem Informasi Pelaporan Kerusakan Jalan di Kota Tomohon - Nindy Gaby Sepang; Nadya Verona Viani Kamasi; Frangky Runtu (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
This research aims to develop a road damage reporting information system in tomohon city, enabling the public to directly report damaged roads and provide input for road repairs from relevant authorities. the design of this information system was developed using Extreme Programming (XP) system development methodology, which consists of four stages: planning, design, coding, and testing. This research resulted in a road damage reporting information system, and based on the prototype testing, it achieved a usability testing feasibility percentage of 92%.